Imaging Ultrasound Technique in Covid-19 Pneumonia - Lilik Lestari (Indonesian Journal of Physics and Nuclear Applications, 2020)
The Covid-19 disease caused by the SARS CoV-2 virus has become an epidemic in Indonesia since President Joko Widodo first announced it in early March 2020. To establish a diagnosis, apart from examining throat swabs, sputum, and Broncho alveolar lavage, chest imaging is also needed. This study aims to report the results of ultrasound (USG) imaging techniques in helping to diagnose Covid-19 disease treated by RSPAW Salatiga. The research method chosen was descriptive-analytic case reports. The study results explained that based on the patient's chest ultrasound, bilateral pneumonia was found in the peripheral lung with pleural thickening following Covid-19 pneumonia, no pleural effusion, and no pericardial effusion.